The relationship between weight-adjusted waist index and peripheral artery disease - Zhe Wu; Yang Liu; Bin Wang (Frontiers in Nutrition)
BackgroundObesity is a significant risk factor for peripheral arterial disease (PAD). The weight-adjusted waist index (WWI) is a novel obesity metric that better reflects abdominal obesity than traditional body mass index (BMI). However, research on the relationship between WWI and PAD remains scarce.MethodsRelevant data from the NHANES 1999–2004 were selected. Multiple logistic regression and restricted cubic spline (RCS) analyses were used to assess the relationship between WWI and the risk of PAD. Additionally, the area under the curve (AUC) of the receiver operating characteristic (ROC) was used to evaluate the predictive ability of WWI for PAD.ResultsA total of 5,686 participants were included in the study, of whom 476 had PAD and 5,210 did not. The results of multiple logistic regression showed that WWI was significantly positively associated with the risk of PAD after full adjustment for covariates (OR: 1.407, 95% CI: 1.100–1.799). Additionally, compared to the first quartile of WWI, the risk of PAD significantly increased in the second quartile (OR: 2.042, 95% CI: 1.333–3.129), third quartile (OR: 2.134, 95% CI: 1.354–3.364), and fourth quartile (OR: 2.491, 95% CI: 1.435–4.325). The ROC results showed that the AUC value for WWI was 0.697, while the AUC value for BMI was 0.520. Compared to BMI, WWI has a better predictive value for the risk of PAD.ConclusionThere is a significant positive correlation between WWI and the risk of PAD. For individuals with high WWI, efforts should be made to reduce WWI to prevent the onset of PAD.